Burnout syndrome and perceptions about safety climate among intensive care professionals - Ana Kele Arcanjo de Sousa; Silvania Braga Ribeiro; Patrícia Freire de Vasconcelos; Roberta Meneses Oliveira; Maria Eliane da Silva; Vanessa Emille Carvalho de Sousa Freire; Vitória Talya dos Santos Sousa (Universidade Federal do Ceará, 2020)
Objective: to analyze the relationship between Burnout Syndrome and perceptions about safety climate among intensive care professionals. Methods: a cross-sectional study with 51 health professionals from a public hospital in northeastern Brazil. The following instruments were applied: the Maslach Burnout Inventory, the Safety Attitudes Questionnaire, and a Sociodemographic questionnaire. Descriptive, analytical (Spearman's test) and inferential statistics were adopted. Results: there was a high level of emotional exhaustion (64.7%) and low levels of depersonalization (74.5%) and personal accomplishment (56.8%) in the Burnout assessment. The safety climate was considered satisfactory, with the Safe Behaviors domain having the highest average. There was a moderate correlation between the Stress recognition and Depersonalization subscales. Conclusion: there was a correlation between safety climate and Burnout in the Stress recognition and Depersonalization dimensions, with the latter being considered a consequence of stressful factors which distance professionals from patients.